By investigation, I mean computation: a framework to investigate the societal dimension of crime - Fielding, Nigel (Trends in organized crime, 2017)
The computational analysis of the societal dimension of crime has aroused an increasing interest in recent years. Data mining, social network analysis (SNA), and visualization techniques are offering promising opportunities to the scientific and investigative study of criminal organizations. In spite of that, the spread of technological innovation faces serious difficulties due to the concurrence of different factors: the absence of user friendly crime analysis tools, the lack of technical skills of investigators (public prosecutors, police officers), two factors that, when combined with the pressure of daily routine, often result into a resistance to change. In this work we present an ongoing research project aiming to foster the potentialities of SNA and computation into criminal investigation. We define an holistic methodology that combines document-enhancement, social network analysis, and visualization techniques to support public prosecutors and criminal investigation departments in exploring the societal dimension of criminal groups. This approach has been deployed in a computational framework, CrimeMiner, validated with a case study based on data coming from real criminal investigations.